SFE Learning Model for High School Mandarin Teachers in Tebing Tinggi City - Julina Julina; Niza Ayuningtias; Rudiansyah Rudiansyah (Randwick International of Education and Linguistics Science Journal, 2021)
This research is entitled 'SFE Learning Model for Mandarin Language Teachers at Senior High Schools in Tebing Tinggi City.' This activity aims to provide assistance in an effort to improve teacher skills in teaching Mandarin to high school students. This teaching training was carried out through a community service program with partner teachers in Tebing Tinggi City High School. This activity started from the anxiety of the principal, where the teacher had not been able to create an attractive and effective learning model. The research used training and mentoring method, starting with socialization activities and then opening in the form of offline motivational seminars. Furthermore, training activities were carried out online using the Zoom Meeting media for two months, involving teachers. The strategy in this activity used the Student Facilitator and Explaining (SFE) type of cooperative learning model. The results of this study are expected to be useful for all teachers in creating an interactive learning atmosphere, with various forms of games and facilitated by current technological advances.